The Role Product Innovation on Business Performance Thought Competitive advantage as Mediation Variable - Saraswati, Thusy Tiara; Sudarmiatin, Sudarmiatin (IJBLE Scientific Publications Community Inc., 2024)
Business is an activity full of competition; having a competitive advantage is essential in achieving success and business survival. This research aims to determine the mediating influence of competitive advantage in product innovation on business performance. The research method uses quantitative exploratory. The population in this study is a regional souvenir and culinary centre with official stalls on the South Ring Road (JLS) Tulungagung - Trenggalek, totaling 236 stalls. Sampling in this study used simple random sampling with 147 respondents. Data analysis used Partial Least Square (PLS) to test direct and indirect effects. The results reveal that product innovation has a direct impact on business performance. Competitive advantage has a direct effect on business performance. Product innovation has a direct impact on competitive advantage. And the last, product innovation has an indirect effect on business performance through competitive advantage. The limitations of this research are the time, costs, and energy expended by researchers due to the long distance between the respondents’ locations. This research suggests that traders in the southern route should innovate their products to sustain their businesses and have a competitive advantage as differentiators from similar businesses in that area